The Green’s Function Method Solutions to Solve of nth-order Linear Differential Equations - Eljaneid, Nedal Hassan Elbadowi; Abdelradi, Abdelradi Abdelrahman; Ibrahim, Ragaa Mohammed Haj (Journal of natural sciences, life and applied sciences, 2020)
In this research article, we present the Green’s function approach of ordinary differential equations with initial and boundary conditions, we represented the differential equation by an integral equation. The text provides a sufficient theoretical basis to understand Green’s function method, which is used to solve initial and boundary value problems involving linear ODEs and PDEs. The main result the construction of a Mathematica Package valid to calculate the explicit expression of the Green’s function related to the two-point boundary value problem (2. 3), where the nth order linear operator Ln defined on (2. 1) has constant coefficients.